Слово авторитета: роман / Евгений Сухов - Сухов Евгений Евгеньевич (ЭКСМО-Пресс, 2001)
Экземпляры: ЦБ (20220311) / Инвентарный номер: 54868 / Цена: 100.00 / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: С 91 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6